Method for manufacturing structure with bumps and substrate having bumps pattern
By forming bumps of organic components and conductive particles on the transfer substrate, and using laser irradiation transfer technology, the bump cracks and contact resistance rise caused by low laser irradiation intensity are solved, and high transferability and reliability are achieved connect.
Patent Information
- Application Number
- CN202380037807.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-26
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the case of low laser irradiation intensity, it is difficult to form bumps with excellent transferability and connection reliability, and small cracks are prone to occur, resulting in rising contact resistance and connection reliability problems.
A bump containing organic components and conductive particles is formed on the transfer substrate having a release layer, and laser irradiation is performed from the opposite side of the transfer substrate to transfer bumps, so that the impact is relieved by the organic components and conductive particles. Improve connection reliability.
Even when the laser irradiation intensity is low, bumps with excellent transferability and high connection reliability can be obtained, which solves the problems of tiny cracks and rising contact resistance.
Smart Images

Figure CN119138109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a structure with bumps and a substrate with bump patterns. Background Art
[0002] In recent years, the miniaturization of electronic components has been advancing, and in particular, the development of technology for manufacturing displays by arranging micro-sized LEDs has become popular. As a technology for mounting LEDs on TFT substrates, a method of forming a bonding material called a "bump" on an electrode to bond the LED electrode to the TFT substrate electrode has been studied.
[0003] As a method for manufacturing a substrate with a conductive pattern suitable for use as a mounting substrate for micro LEDs, for example, the following method for manufacturing a substrate with a conductive pattern has been proposed, which includes: a process of forming a pattern of a composition having an organic component and conductive particles on a transfer substrate; and a process of transferring the pattern to a transferred substrate by irradiating a laser from the back side of the transfer substrate (for example, see patent document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-55760 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The manufacturing method described in Patent Document 1 can form a highly conductive conductive pattern with good positional accuracy. However, according to the research of the inventors of this application, it has been found that if the micro-LED is transferred by laser irradiation, tiny cracks are easily generated inside the bump due to the impact during transfer. Especially after the electronic components are installed, if they are exposed to an environment with repeated temperature changes, peeling and increased contact resistance will occur starting from the tiny cracks, which will cause problems in connection reliability. In order to alleviate the impact during transfer, it is effective to reduce the laser irradiation intensity, but according to the method described in Patent Document 1, transfer is difficult when the laser irradiation intensity is low.
[0009] Therefore, the object of the present invention is to provide a method for manufacturing a structure with bumps, and a substrate with a bump pattern preferably used for the manufacturing method, wherein the method for manufacturing a structure with bumps can form bumps with excellent transferability and high connection reliability even when the laser irradiation intensity is low.
[0010] Means for solving problems
[0011] The present invention is a method for manufacturing a structure with bumps, which comprises: a process of forming bumps containing organic components and conductive particles on a release layer of a transfer substrate having a release layer (bump forming process); and a process of irradiating a laser from the opposite side of the release layer of the transfer substrate to transfer the bumps to an electrode portion of a substrate with electrodes or an electronic component (bump transfer process).
[0012] The present invention also provides a substrate having a bump pattern containing an organic component and conductive particles on a release layer of a transfer substrate having a release layer.
[0013] Effects of the Invention
[0014] According to the present invention, even when the laser irradiation intensity is low, it is possible to obtain a structure with bumps having excellent transferability and high connection reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] [ Figure 1 ] is a schematic diagram showing an example of a method for manufacturing a structure with bumps according to the present invention.
[0016] [ Figure 2 ] is a schematic diagram showing an application example of the method for manufacturing a structure with bumps according to the present invention.
[0017] [ Figure 3 ] is a schematic cross-sectional view of a printed wiring board with bumps obtained in the embodiment.
[0018] [ Figure 4 ] is a schematic cross-sectional view of the conductivity evaluation sample used in the examples. DETAILED DESCRIPTION
[0019] The structure with bumps in the present invention has bumps containing organic components and conductive particles on the electrode portion of the substrate with electrodes or the electronic component. As described above, the bumps have the function of bonding the electrodes to each other. The structure with bumps can be suitably used as a substrate for mounting electronic components such as micro LEDs, etc.
[0020] The method for manufacturing a structure with bumps according to the first embodiment of the present invention comprises: a step of forming bumps containing organic components and conductive particles on a release layer of a transfer substrate having a release layer (bump forming step); and a step of transferring the bumps to an electrode portion of a substrate with electrodes or an electronic component by irradiating a laser from the opposite side of the release layer of the transfer substrate (bump transfer step). It should be noted that, for convenience, the bumps (bumps before transfer) provided on the release layer of the transfer substrate are sometimes referred to as bump patterns. By making the bumps contain organic components and conductive particles, the impact in the bump transfer process can be mitigated and the connection reliability can be improved. Furthermore, since the transfer substrate has a release layer, the transferability is excellent even when the laser irradiation intensity is low. Therefore, according to the present invention, the impact in the bump transfer process can be mitigated and the connection reliability can be improved.
[0021] Figure 1 A schematic diagram showing an example of a method for manufacturing a structure with bumps of the present invention. (a) shows a bump forming process, in which a bump 1 is formed on a release layer 5 on a glass substrate 2. (b) shows a bump transfer process, in which a laser 3 is irradiated from the opposite side of the release layer 5 of the glass substrate 2. The bump 1 peeled off from the release layer 5 by irradiation with the laser 3 is transferred to an electrode portion of a transferred substrate 4. Here, the electrode portion refers to a connection portion in a substrate or electronic component with an electrode that is exposed in order to send an electrical signal to the substrate wiring or the electronic component. For example, when a bump is formed directly on a substrate wiring, the substrate wiring is used as the electrode portion.
[0022] The substrate with a bump pattern according to the second embodiment of the present invention has a bump pattern containing an organic component and conductive particles on a release layer of a transfer substrate having a release layer. The substrate can be suitably used in a method for manufacturing a structure with bumps. Specifically, by subjecting the substrate with a bump pattern according to the present invention to the bump transfer step in the first embodiment of the present invention, a structure with bumps can be manufactured.
[0023] Hereinafter, each step of the method for producing a structure with bumps according to the present invention will be described.
[0024] <Bump Forming Process>
[0025] Bumps (bump pattern) containing an organic component and conductive particles are formed on the release layer of the transfer substrate having the release layer.
[0026] The transfer substrate may be any substrate that is translucent to the laser wavelength described below. For example, a glass substrate, a quartz substrate, a sapphire substrate, etc. Among these, a glass substrate that is easily available is preferred.
[0027] As a method for forming a release layer on a transfer substrate, for example, there can be mentioned a method of applying a release agent solution prepared by diluting a release agent with a solvent on the transfer substrate and removing the solvent. As a coating method, for example, there can be mentioned a coating method using a die coater, a spin coating method, etc. As a method for removing the solvent, for example, there can be mentioned heating and drying, etc.
[0028] As the release agent for forming the release layer, for example, aminoalkyd-based release agents, long-chain alkyl-based release agents, silicone-based release agents, fluorine-based release agents, etc. can be cited. Two or more of these can also be used. More specifically, aminoalkyd-based release agents such as "Tesfine (registered trademark)" 303, "Tesfine (registered trademark)" 305, and "Tesfine (registered trademark)" 314 manufactured by Showa Denko Materials Co., Ltd., "Tesfine (registered trademark)" 319, TA31-209E manufactured by Showa Denko Materials Co., Ltd., KS-702, KS-707 manufactured by Shin-Etsu Chemical Co., Ltd., AGC Seimi Fluorine-based mold release agents such as F-6711-AL, F-6758-AL, F-6441L-AL, EF-6521-AL, F-6811-AL, SFE-DP02H, SFE-B002H, SFE-X008, KTS-3000H, SNF-AF180E, SR-4000A, SW-930, and SWK-601 manufactured by Chemical Co., Ltd. and long-chain alkyl-based mold release agents such as "Peeloil (registered trademark)" 1010, "Peeloil (registered trademark)" 1050, and "Peeloil (registered trademark)" 1070 manufactured by Lion Chemical Co., Ltd. Among these, aminoalkyd-based release agents or fluorine-based release agents are preferred from the perspective of not easily causing adverse effects on the connection reliability after installation even when the release agent transfer occurs in the bump transfer process, and from the perspective of easily adjusting the peeling force and contact angle described later to the preferred numerical range described later. From the perspective of suppressing the generation of pinholes, the thickness of the release layer is preferably 50 nm or more. On the other hand, from the perspective of suppressing the transfer of the release agent in the bump transfer process, the thickness of the release layer is preferably 1,000 nm or less.
[0029] From the viewpoint of appropriately maintaining the adhesion between the bump and the release layer and improving the process margin in the bump transfer process, the peeling force of the transfer substrate with the release layer at 25°C is preferably 100mN / 50mm or more. On the other hand, from the viewpoint of improving the positional accuracy in the transfer process, the peeling force of the transfer substrate with the release layer at 25°C is preferably 5,000mN / 50mm or less. Here, the peeling force of the transfer substrate in the present invention refers to the peeling force when the acrylic adhesive tape "31B" manufactured by Nitto Denko Corporation is attached to the release layer forming surface of the transfer substrate using a 2kg roller and left to stand for 30 minutes, and then the acrylic adhesive tape is peeled off under the conditions of a temperature of 25°C, a peeling angle of 180°, and a peeling speed of 0.3m / min. As a means for making the peeling force within the above range, for example, a release agent listed above as a preferred release agent can be cited.
[0030] From the viewpoint of improving the process margin in the bump transfer process, the water contact angle of the release layer at 25°C is preferably 80 degrees or more, and more preferably 90 degrees or more. On the other hand, from the viewpoint of suppressing depressions and pinholes in the bump formation process and improving the process margin in the bump transfer process, the water contact angle of the release layer at 25°C is preferably 140 degrees or less, and more preferably 110 degrees or less. The water contact angle of the release layer can be measured in accordance with JIS R3257 (1999) using a commercially available contact angle measuring device such as "CA-Z" manufactured by Kyowa Interface Chemical Co., Ltd.
[0031] As a method for forming a bump pattern on a release layer, for example, pattern printing, inkjet coating, laser etching, photolithography, etc. can be cited. Pattern printing is a method for printing an organic component and conductive particles in a pattern on a release layer using screen printing, gravure printing, etc. Laser etching is a method for removing unnecessary parts using laser etching after printing a rough pattern of organic components and conductive particles. Photolithography is a method for forming a bump pattern using a photosensitive composition as a composition containing an organic component and conductive particles and through a process (exposure process) of exposing the photosensitive composition and a process (development process) of developing. Among these, from the viewpoint of being able to perform fine patterning and improving the positional accuracy in the bump transfer process, photolithography is preferred.
[0032] As the light source in the exposure step, a mercury lamp, i-line (365 nm), or h-line (405 nm) of an LED is preferably used.
[0033] As the developer in the development step, for example, alkaline developers such as aqueous solutions of tetramethylammonium hydroxide, diethanolamine, diethylaminoethanol, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, methylamine, dimethylamine, dimethylaminoethyl acetate, dimethylaminoethanol, dimethylaminoethyl methacrylate, cyclohexylamine, ethylenediamine, and hexamethylenediamine can be cited.
[0034] The shape of the bump pattern is not particularly limited, and examples thereof include a rectangular shape, a circular shape, an elliptical shape, a triangular shape, a polygonal shape, and a combination of these shapes in plan view.
[0035] From the viewpoint of further suppressing the generation of micro cracks in the bump transfer process and further improving the connection reliability, the thickness of the bump pattern in the bump forming process is preferably 1 μm or more. On the other hand, from the viewpoint of suppressing the expansion of the bump when mounting the electronic component, suppressing the short circuit with the surrounding electrodes, and improving the position accuracy in the bump transfer process, the thickness of the bump pattern is preferably 5 μm or less.
[0036] Here, the thickness of the bump pattern in the bump forming process refers to the average value of the heights of 10 randomly selected bumps calculated by regarding the pattern shape as a rectangle. More specifically, for 10 bump patterns randomly selected from the bump patterns formed in the bump forming process, the surface is laser scanned at a magnification of 500 to 1,000 times using a laser microscope VK-X250 manufactured by Keyence Co., Ltd., and the surface shape is measured. The thickness of the bump pattern can be measured by regarding the pattern shape as a rectangle and calculating the height of the bump pattern and calculating the average value thereof according to the analysis mode attached to the device.
[0037] From the viewpoint of further suppressing the generation of micro cracks in the bump transfer process and further improving the connection reliability, the aspect ratio of the bump pattern in the bump forming process is preferably greater than 0.1. On the other hand, from the viewpoint of further improving the directivity in the bump transfer process and improving the position accuracy, the aspect ratio of the bump pattern is preferably less than 0.4.
[0038] Here, the aspect ratio of the bump pattern in the bump forming process refers to the average value of the value obtained by dividing the bump pattern thickness by the bump pattern diameter for 10 randomly selected bump patterns. It should be noted that if the bump is cylindrical, the diameter is taken as the bump pattern diameter, and in the case of other than cylindrical shapes, the diameter when converted into a cylinder with equal contact area is taken as the bump pattern diameter.
[0039] From the viewpoint of improving the positional accuracy, the contact area between the bump pattern and the release layer in the bump formation step is preferably 25 μm per bump pattern. 2On the other hand, from the viewpoint of uniformly generating ablation at the contact interface during laser irradiation and improving positional accuracy, the contact area between the bump pattern and the release layer is preferably 500 μm 2 As follows. Here, the contact area between the bump and the release layer in the bump forming process refers to the average value of the contact area between 10 randomly selected bump patterns and the release layer. More specifically, for the bump pattern, an optical microscope is used to observe at a magnification of 500 to 1,000 times to obtain an image, and the image obtained is binarized using image analysis and measurement software based on the brightness of the measurement image. The dark portion in the binarized image is used as the contact portion between the transfer substrate and the bump pattern, and the area of the dark portion is calculated. For 10 randomly selected bump patterns, the contact area with the release layer is calculated, and the average value is used as the contact area between the bump pattern and the release layer. It should be noted that regarding the contact area between the bump pattern and the release layer, for example, when the bump pattern is formed by photolithography, it can be set to a desired range by adjusting the size of the mask, etc.
[0040] From the perspective of limiting the laser reaching the bump pattern to the vicinity of the release layer, improving the positional accuracy of the bump transfer process, and expanding the process margin, the optical density (optical density, hereinafter referred to as "OD value") of the bump pattern in the bump formation process is preferably greater than 0.5 in the visible light region with a wavelength of 380nm to 700nm, and more preferably greater than 1. On the other hand, from the perspective of connection reliability, the OD value of the bump pattern is preferably less than 3. Here, the OD value of the bump pattern in the present invention refers to the average value of the OD values of 5 randomly selected bump patterns. More specifically, it can be obtained as follows: for 5 bump patterns randomly selected from the transfer substrate, the transmitted light intensity at a wavelength of 532nm is measured using a microspectrometer, and the respective OD values are obtained according to the following relationship (1), and the average value is calculated.
[0041] OD value = log10 (I0 / I) (1)
[0042] Here, I0 represents the incident light intensity, and I represents the transmitted light intensity.
[0043] The bump contains an organic component and conductive particles. When the bump pattern is formed by the above-mentioned photolithography method having an exposure step and a development step, it is preferable to contain a photosensitive organic component as the organic component. As the photosensitive organic component, for example, a resin, a monomer, a photopolymerization initiator, etc. having a photoreactive group can be cited.
[0044] Examples of the organic component include acrylic copolymers, phenol Novolac resins, cresol Novolac resins, epoxy resins, urethane resins, polyimide resins, polyamic acids, polyamide resins, and siloxane resins. Among these, acrylic copolymers are preferred when used in a photosensitive composition from the viewpoint of photosensitivity.
[0045] When the alkaline developer is used in the development process, as an organic component, a combination of a carboxyl-containing acrylic copolymer, a compound having a photoreactive group, and a photopolymerization initiator; a combination of a phenol Novolac resin or a cresol Novolac resin and a photoacid generator; a combination of a polyamic acid and a photoacid generator; a combination of a polyimide resin, a compound having a photoreactive group, and a photopolymerization initiator, etc. Among these, a combination of a carboxyl-containing acrylic copolymer, a compound having a photoreactive group, and a photopolymerization initiator is preferred, which is easy to form a bump with high mounting performance and a low glass transition temperature. In the above combination, it is more preferred that the carboxyl-containing acrylic copolymer has a photoreactive group, which can improve the strength of the bump by making the photosensitivity excellent and increasing the crosslinking density of the exposure part, further suppressing the generation of microcracks in the bump transfer process, and further improving the connection reliability. In addition, it is preferred to further contain an epoxy compound as a thermosetting component, which can improve the adhesion between the electrodes and further improve the connection reliability.
[0046] The carboxyl group-containing acrylic resin is prepared by copolymerizing an acrylic monomer, which is a compound having a photoreactive group, with an unsaturated acid. Examples of the acrylic monomer include methyl acrylate, ethyl acrylate (hereinafter, sometimes referred to as "EA"), 2-ethylhexyl acrylate, n-butyl acrylate (hereinafter, sometimes referred to as "BA"), isobutyl acrylate, isopropyl acrylate, glycidyl acrylate, butoxytriethylene glycol acrylate, dicyclopentyl acrylate, dicyclopentenyl acrylate, 2-hydroxyethyl acrylate, isobornyl acrylate, 2-hydroxypropyl acrylate, isodecyl acrylate, isooctyl acrylate, lauryl acrylate, 2-methoxyethyl acrylate, methoxyethylene glycol acrylate, methoxydiethylene glycol acrylate, octafluoropentyl acrylate, phenoxyethyl acrylate, stearyl acrylate, trifluoroethyl acrylate, aminoethyl acrylate, phenyl acrylate, phenoxyethyl acrylate, 1-naphthyl acrylate, 2-naphthyl acrylate, thiophenol acrylate, benzyl mercaptan acrylate, and compounds obtained by replacing the acryloyl groups of these with methacryloyl groups. Two or more of these may be used. Examples of the unsaturated acid include acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, and fumaric acid.
[0047] The content of the carboxyl-containing acrylic resin in the organic component is preferably 20 to 70% by weight of the solid component. Here, the so-called solid component refers to the components other than the solvent in the organic component. If the content of the carboxyl-containing acrylic resin in the organic component solid component is 20% to 70% by weight, the solubility in the developer can be appropriately maintained, thereby enabling fine pattern processing.
[0048] As the compound having a photoreactive group, an acrylic monomer is preferably used, for example, an acrylic monomer exemplified as a raw material of the above-mentioned carboxyl-containing acrylic resin can be cited. The content of the compound having a photoreactive group in the organic component is preferably 5 to 30% by weight in the solid component. If the content of the compound having a photoreactive group is 5% by weight or more, the curing density of the exposed part increases, so the residual film rate after development can be increased, and fine patterning can be performed. On the other hand, if the content of the compound having a photoreactive group is less than 30% by weight, the bump pattern formed will not become too hard, and the adhesion with the electronic component will be improved, thereby improving the connection reliability.
[0049] Examples of the photopolymerization initiator include benzophenone derivatives, acetophenone derivatives, thioxanthone derivatives, benzyl derivatives, benzoin derivatives, oxime compounds, α-hydroxyketone compounds, α-aminoalkylphenone compounds, phosphine oxide compounds, anthrone compounds, anthraquinone compounds, etc. Among them, oxime compounds having high photosensitivity are preferred. Examples of oxime compounds include 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyl oxime)], ethyl ketone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetyl oxime), 1-phenyl-1,2-butanedione-2-(O-methoxycarbonyl)oxime, 1-phenyl-propanedione-2-(O-ethoxycarbonyl)oxime, 1-phenyl-propanedione-2-(O-benzoyl)oxime, 1,3-diphenyl-propanetrione-2-(O-ethoxycarbonyl)oxime, and 1-phenyl-3-ethoxy-propanetrione-2-(O-benzoyl)oxime. Two or more of these may be contained.
[0050] The content of the photopolymerization initiator in the organic component is preferably 1 to 10% by weight of the solid component. If the content of the photopolymerization initiator is 1% by weight or more, the curing density of the exposed portion increases, thereby increasing the residual film rate after development and enabling fine patterning. On the other hand, if the content of the photopolymerization initiator is 10% by weight or less, the side edge caused by excessive light absorption caused by the photopolymerization initiator at the upper part of the coated dry film during exposure can be suppressed, thereby further improving fine processability and transfer position accuracy of laser transfer.
[0051] Examples of epoxy compounds include glycidyl ethers, glycidyl amines, and epoxy resins. More specifically, examples of glycidyl ethers include methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, bisphenol fluorene diglycidyl ether, biphenol diglycidyl ether, tetramethyl biphenol glycidyl ether, trimethylolpropane triglycidyl ether, and 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate. Examples of glycidyl amines include tert-butyl glycidyl amine. Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, Novolac epoxy resin, and hydrogenated bisphenol A epoxy resin. Two or more of these may be used.
[0052] The content of the epoxy compound in the organic component is preferably 5 to 50% by weight of the solid component. If the content of the epoxy compound is 5% by weight or more, the adhesion between the substrate and the electronic component is improved, thereby improving the connection reliability. On the other hand, if the content of the epoxy compound is 50% or less, the photocuring reaction during exposure proceeds smoothly, the crosslinking density becomes high, and thus a fine pattern can be formed.
[0053] In the present invention, by having conductive particles in the bump, the conductive particles form a three-dimensional conductive path with each other after installation, showing high conductivity. As conductive particles, for example, particles containing metals such as silver, gold, copper, platinum, lead, tin, nickel, aluminum, tungsten, molybdenum, chromium, titanium, indium, their alloys, ITO, tin oxide, antimony-doped tin oxide, carbon black, etc. can be cited. In addition, materials having a coating layer formed by the above-mentioned metals and carbon on the surface of insulating particles such as resins and inorganic oxides and conductive particles can also be cited. Two or more of these can be contained. Among these, carbon black or metal particles with a carbon coating layer are preferably considered from the aspects of having an absorption region in the laser wavelength, efficiently converting the energy during laser irradiation into heat, and easily decomposing the organic components of the bump located at the interface of the demolding layer, and excellent laser transferability. Furthermore, carbon black can be stably electrically connected to molybdenum and ITO that are difficult to electrically connect, so it is preferred.
[0054] From the viewpoint of increasing the contact probability between the conductive particles, the aspect ratio of the conductive particles is preferably 1.0 or more. On the other hand, from the viewpoint of suppressing the shielding of the exposure light in the exposure process and expanding the development margin in the development process, the aspect ratio of the conductive particles is preferably 3.0 or less, and more preferably 2.0 or less. Here, the aspect ratio of the conductive particles is the value obtained by dividing the major axis length of the conductive particles by the minor axis length. The conductive particles are magnified and observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) at a magnification of 15,000 times, and the major axis length and the minor axis length of each of the primary particles of 100 randomly selected conductive particles are measured, and the number average of the aspect ratios obtained by the two is taken as the aspect ratio of the conductive particles.
[0055] From the perspective of dispersibility in the photosensitive composition, the particle size of the conductive particles is preferably 0.03 μm or more. On the other hand, from the perspective of further improving the surface smoothness, pattern accuracy and dimensional accuracy of the bumps, and the positional accuracy in the bump transfer process, the particle size of the conductive particles is preferably 1.0 μm or less, more preferably 0.2 μm or less. Here, the particle size of the conductive particles can be obtained by a dynamic light scattering method. Specifically, it can be obtained by irradiating a dispersion having a conductive particle concentration of 5 to 30% by volume with light of a wavelength of 780 nm using a semiconductor laser, measuring the scattered light, and performing frequency analysis by FFT-heterodyne method.
[0056] From the viewpoint of improving conductivity, the content of conductive particles in the bump is preferably 10% by volume or more, more preferably 15% by volume or more. On the other hand, from the viewpoint of further improving the positional accuracy in the bump transfer process by appropriately containing an organic component, further alleviating the impact in the bump transfer process, further improving the connection reliability, and improving the bonding strength between the electronic component and the structure with the bump, the content of conductive particles is preferably 40% by volume or less, more preferably 30% by volume or less.
[0057] Here, the content of conductive particles in the bump can be measured as follows. Scrape off the bump on the transfer substrate to prepare a measurement sample. Use a thermogravimetric analyzer to keep the measurement sample in the atmosphere at 600°C for 1 hour to remove the organic components, and calculate the weight ratio of the remaining portion in the measurement sample (thermogravimetric analysis residual rate) and the weight ratio of the removed portion in the measurement sample (thermogravimetric analysis reduction rate). Using the thermogravimetric analysis residual rate as the weight fraction of the conductive particles and the thermogravimetric analysis reduction rate as the weight fraction of the organic components, the content of conductive particles in the bump (volume %) can be calculated using the following formula [1]. Here, the density of the organic component is set to 1.1 g / cm 3When the composition ratio of the raw materials of the organic component and the conductive particles in the bump is known, the content (volume %) of the conductive particles in the bump can be calculated based on the composition ratio.
[0058] [Mathematical formula 1]
[0059]
[0060] The bumps or the photosensitive composition used for forming the bumps may contain additives such as a plasticizer, a leveling agent, a surfactant, a silane coupling agent, a defoaming agent, and a pigment within a range not impairing the desired properties.
[0061] It should be noted that the description of the transfer substrate, the release layer and the bump pattern in this process is the same as the transfer substrate, the release layer and the bump pattern of the substrate with a bump pattern of the second embodiment of the present invention. In addition, this process is also equivalent to the manufacturing method of the substrate with a bump pattern as the second embodiment of the present invention.
[0062] <Bump Transfer Process>
[0063] Next, laser is irradiated from the opposite side of the release layer of the transfer substrate to transfer the bumps to the electrode portion of the substrate with electrodes or the electronic component. In this step, the organic components and conductive particles contained in the bumps are heated by the laser that passes through the transfer substrate, so that the organic components of the bumps located at the interface of the release layer of the transfer substrate are decomposed, thereby transferring the bumps from the release layer to the electrode portion of the substrate with electrodes or the electronic component.
[0064] In the present invention, the release layer provides excellent transferability even when the laser irradiation intensity is low, so that decomposition of organic matter and impact of bumps caused by laser irradiation can be suppressed, and bumps with high connection reliability can be formed.
[0065] As the irradiated laser, any laser that can utilize the heat generated by the irradiation to decompose the organic components of the transfer substrate interface can be used. For example, a laser with a wavelength range of 257nm to 1900nm can be cited. Among these, from the viewpoint of transferability, a solid laser with a wavelength of 355nm or 532nm is preferred. The output of the laser is preferably 200 to 600mJ. If the output of the laser is more than 200mJ, it is not easily affected by the uneven adhesion between the bump and the release layer, and the position accuracy in the transfer process can be improved. On the other hand, if the output of the laser is less than 600mJ, the impact in the bump transfer process can be further alleviated, and the connection reliability can be further improved. The output of the laser is more preferably less than 500mJ.
[0066] From the viewpoint of further improving the positional accuracy in the bump transfer process, the contact area between the substrate with electrodes or the electronic component to which the bump is transferred and the bump is preferably 20 μm on average per bump. 2 On the other hand, from the viewpoint of suppressing the temperature unevenness of the bumps caused by laser irradiation and improving the positional accuracy, the contact area is preferably 500 μm 2 As follows. Here, the contact area between the bump and the substrate or electronic component with electrode in the present invention refers to the average value for 10 randomly selected bumps. The substrate or electronic component with electrode including the bump is magnified and observed and photographed at a magnification of 500 to 1,000 times using an optical microscope, and the obtained image is binarized based on the brightness of the image for measurement using image analysis and measurement software. The dark portion in the binarized image is equivalent to the contact portion between the substrate or electronic component with electrode and the bump, and the area of the dark portion is calculated. The contact area is calculated for 10 randomly selected bumps, and the average value is taken as the contact area between the substrate or electronic component with electrode and the bump. Regarding the contact area, for example, when the bump is formed by photolithography, it can be adjusted to the desired range by adjusting the size of the mask, etc.
[0067] The substrate with electrodes to which the bumps are transferred is preferably a TFT substrate having electrodes made of a material selected from molybdenum, titanium and ITO, a printed wiring board having copper electrodes, etc. The electronic component to which the bumps are transferred is preferably an LED chip having gold electrodes, etc.
[0068] The electrode contacted by the transferred bump preferably contains a material selected from molybdenum, titanium and ITO in view of the low generation of ion migration and intermetallic compounds. The electrode containing the above materials can be preferably used when carbon black is used as the conductive particles contained in the bump in view of the high connection reliability with carbon black.
[0069] According to the method for manufacturing a structure with bumps of the present invention, bumps can be formed only in a specific narrow area on a substrate. As an example of forming bumps only in a specific narrow area on a substrate, Figure 2 A schematic diagram of an application example of the method for manufacturing a structure with bumps of the present invention is shown in FIG. Figure 2 As shown in (a) in the figure, sometimes after mounting a plurality of electronic components 14 on a transferred substrate 13 as a substrate with electrodes by bonding bumps 10 to the electrodes 15 of the electronic components, a defective specific electronic component 14' is confirmed. In this case, a repair operation is performed to remove the defective electronic component 14' and mount a new electronic component at the location.
[0070] At this time, in order to mount new electronic components, it is necessary to form new bumps on the substrate. Figure 2As shown in (a) in FIG. 1 , there are other electronic components 14 on the substrate other than the removed defective electronic component 14. Therefore, since the area available for forming bumps is narrow and the concavities and convexities on the transferred substrate 13 are large, it is difficult to form bumps by photolithography using a photosensitive composition.
[0071] On the other hand, according to the present invention, by Figure 2 As shown in (b) in FIG. 1 , a transfer substrate 11 having a release layer 5 and having a bump 10 formed thereon is used and irradiated with a laser beam 12 to obtain a Figure 2 As shown in (c) in FIG. 1 , bumps are formed only on the missing portion of the electronic component 14 ′. That is, bumps can be formed on the transferred substrate 13 on which the electronic component 14 is mounted without being affected by the unevenness due to the electronic component 14 .
[0072] The method for producing a structure with bumps and the substrate with a bump pattern of the present invention are suitably used, for example, when manufacturing a substrate for mounting LEDs. The substrate with a bump pattern of the present invention can be suitably used for the above-mentioned repair application.
[0073] Example
[0074] Hereinafter, the present invention will be described by way of examples, but the embodiments of the present invention are not limited thereto.
[0075] The evaluation method in each example is as follows.
[0076] <Contact Area between Bump and Release Layer in Bump Formation Step>
[0077] In each embodiment and comparative example, after forming bumps on the release layer of the transfer substrate, 10 randomly selected bumps were photographed at a magnification of 500 to 1,000 times using a microscope VHX-5500 manufactured by Keyence Co., Ltd., and binarized based on the brightness of the measurement image in the image analysis mode. The dark portion in the binarized image was assumed to correspond to the contact portion between each bump and the release layer, and the area of the dark portion was calculated. The contact area of each bump with the release layer was obtained by calculating the average of the areas of the dark portions for the 10 bumps.
[0078] <Peeling force of transfer substrate with release layer>
[0079] An acrylic adhesive tape "31B" manufactured by Nitto Denko Corporation was attached to the release layer of the transfer substrate prepared in each embodiment and comparative example using a 2 kg roller and allowed to stand for 30 minutes. The adhesive tape was then peeled off at a temperature of 25°C, a peeling angle of 180°, and a peeling speed of 0.3 m / min, and the peeling force at this time was measured.
[0080] <Water contact angle of release layer>
[0081] The release layer of the transfer substrate produced in each of the Examples and Comparative Examples was measured for water contact angle at 25° C. using a contact angle measuring apparatus “CA-Z” manufactured by Kyowa Interface Chemical Co., Ltd. in accordance with JIS R3257 (1999).
[0082] <OD Value of Bump in Bump Formation Process>
[0083] In each embodiment and comparative example, after forming the bumps on the release layer of the transfer substrate, the intensity of the transmitted light at a wavelength of 532 nm was measured for 5 randomly selected bumps using a microspectrometer (MSV-5500 manufactured by JASCO Corporation), and the OD value of each bump was calculated based on the transmitted light intensity. For the 5 bumps, the average value was calculated as the OD value of the bump.
[0084] <Position accuracy in transfer process>
[0085] For 10 bumps randomly selected from the glass substrate with bumps obtained from each embodiment and comparative example, the bumps were observed from the surface opposite to the surface on which the bumps were formed using an optical microscope, and the offset between the center of the bump and the intersection of the cross mark of the transferred object was measured. For the 10 bumps, the average value was calculated. It should be noted that the smaller the difference in offset between 300mJ irradiation and 600mJ irradiation, the higher the process margin.
[0086] <Conductivity>
[0087] On the printed wiring board with bumps obtained in each example and comparative example, a 3 mm square silicon chip with electrodes was thermocompressed for 5 seconds at a temperature of 120°C and a pressure of 1 MPa, and then heated in an oven at a temperature of 140°C for 30 minutes. Figure 4 The silicon chip mounting substrate shown has electrodes 9 of a silicon chip 8 bonded to electrodes 7 of a printed wiring board 6 having bumps 1. Then, a point a and a point b of the printed wiring board with bumps are connected by a tester to measure the resistance value.
[0088] <Connection Reliability>
[0089] The silicon chip mounting substrate prepared in the above <Conductivity> evaluation was placed in a heating and cooling process at -55°C and 125°C for 1 hour each as one cycle and 500 cycles were performed, and then the resistance value was measured in the same manner as in the above <Conductivity>. The change in resistance value before and after the heating and cooling process was calculated by the following formula to evaluate the connection reliability. It can be said that the closer the change in resistance value is to 1, the higher the connection reliability.
[0090] Resistance value change = resistance value after heating and cooling / resistance value before heating and cooling.
[0091] The materials used in Examples and Comparative Examples are as follows.
[0092] [Release agent]
[0093] "Tesfine (registered trademark)" 303: Aminoalkyd-based mold release agent manufactured by Showa Denko Materials Co., Ltd.
[0094] · "Tesfine (registered trademark)" 319: Silicone-based mold release agent manufactured by Showa Denko Materials Co., Ltd.
[0095] ·F-6711-AL: Fluorine-based mold release agent manufactured by AGC Seimi Chemical Co., Ltd.
[0096] ·SFE-DP02H: Fluorine-based mold release agent manufactured by AGC Seimi Chemical Co., Ltd.
[0097] ·SFE-X008: Fluorine-based mold release agent manufactured by AGC Seimi Chemical Co., Ltd.
[0098] ·KTS-3000H: Fluorine-based mold release agent manufactured by AGC Seimi Chemical Co., Ltd.
[0099] SR-4000A: Fluorine-based mold release agent manufactured by AGC Seimi Chemical Co., Ltd.
[0100] · "Peeloil (registered trademark)" 1010: A long-chain alkyl-based mold release agent manufactured by Lion Chemical Co., Ltd.
[0101] [Conductive particles]
[0102] Ag particles: Ag particles manufactured by DOWA Electronics Co., Ltd. (average particle size 300 nm, specific gravity 10 g / cm 3 )
[0103] Tin oxide particles: Tin oxide particles manufactured by Mitsubishi Materials Electronics Co., Ltd. (volume average particle size 300 nm, specific gravity 7.0 g / cm 3 )
[0104] Carbon black particles: Carbon black particles manufactured by Cabot Corporation (average particle size 50 nm, specific gravity 1.9 g / cm 3 )
[0105] Carbon-coated Ag particles: Carbon-coated Ag particles manufactured by Nissin Engineering Co., Ltd. (average thickness of the surface carbon coating layer 1 nm, average particle size 40 nm, specific gravity 9.5 g / cm 3 )
[0106] [Thermosetting resin]
[0107] · EPICLON (registered trademark) N-770: Phenol Novolac type epoxy resin manufactured by DIC Corporation (hereinafter referred to as N-770).
[0108] (Synthesis Example 1: Organic Component Solution A-1)
[0109] 150 g of propylene glycol monomethyl ether acetate (hereinafter referred to as "PGMEA") was placed in a reaction container under a nitrogen atmosphere, and the temperature was raised to 80°C using an oil bath. A mixture containing 20 g of ethyl acrylate (hereinafter referred to as "EA"), 40 g of 2-ethylhexyl methacrylate (hereinafter referred to as 2-EHMA), 20 g of n-butyl acrylate (hereinafter referred to as BA), 15 g of acrylic acid (hereinafter referred to as "AA"), 0.8 g of 2,2'-azobisisobutyronitrile and 10 g of PGMEA was added dropwise over a period of 1 hour. After the addition was completed, the mixture was further heated at 80°C for 6 hours for polymerization reaction. Then, 0.2 g of hydroquinone monomethyl ether was added to stop the polymerization reaction. Next, a mixture containing 5 g of glycidyl methacrylate, 1 g of triethylbenzylammonium chloride and 10 g of PGMEA was added dropwise over a period of 0.5 hours. After the addition was completed, the mixture was further heated for 2 hours for addition reaction. Then, the reaction container was set to an air atmosphere, 5 g of a photopolymerization initiator "Irgacure (registered trademark)" OXE03 (manufactured by BASF) and 20 g of an acrylic monomer "Aronix (registered trademark)" M-315 (manufactured by Toagosei Co., Ltd.) were added, and the mixture was heated and dissolved at 50°C for 3 hours to obtain an organic component solution (A-1) having a solid content of 42.8% by weight.
[0110] (Synthesis Example 2: Organic Component Solution A-2)
[0111] 150 g of PGMEA was placed in a reaction container in a nitrogen atmosphere and heated to 80°C using an oil bath. A mixture of 20 g of EA, 20 g of 2-EHMA, 20 g of BA, 5 g of hydroxymethyl acrylamide, 25 g of AA, 0.8 g of 2,2'-azobisisobutyronitrile and 10 g of PGMEA was added dropwise over a period of 1 hour. After the addition was completed, the polymerization reaction was further carried out by heating at 80°C for 6 hours. Then, 0.2 g of hydroquinone monomethyl ether was added to stop the polymerization reaction. After the reaction container was made into an atmospheric atmosphere, 5 g of a photopolymerization initiator "Irgacure" OXE03 (manufactured by BASF) and 20 g of an acrylic monomer "Aronix (registered trademark)" M-315 (manufactured by Toagosei Co., Ltd.) were added and dissolved by heating at 50°C for 3 hours to obtain an organic component solution (A-2) having a solid content of 42.0% by weight.
[0112] (Synthesis Example 3: Carbon Black Dispersion B-1)
[0113] 13.7 g of carbon black particles, 4 g of dispersant "DISPERBYK (registered trademark)"-21116 (manufactured by BYK-Chemie) and 200 g of PGMEA were mixed and mixed using a homogenizer at 1,200 rpm for 30 minutes. Then, a high-pressure wet medium-free micronizer "Nanomizer" (Nanomizer Co., Ltd.) was used for dispersion treatment to obtain a carbon black dispersion B-1 having an average particle size of 0.15 μm and a conductive particle content of 6.3% by weight.
[0114] (Synthesis Example 4: Ag Particle Dispersion Liquid B-2)
[0115] 80 g of Ag particles, 4 g of dispersant "DISPERBYK (registered trademark)"-21116 (manufactured by BYK-Chemie) and 200 g of PGMEA were mixed and mixed using a homogenizer at 1,200 rpm for 30 minutes. Then, a high-pressure wet medium-free micronizer "Nanomizer" (Nanomizer Co., Ltd.) was used for dispersion treatment to obtain Ag particle dispersion B-2 having an average particle size of 0.6 μm and a conductive particle content of 28.2% by weight.
[0116] (Synthesis Example 5: Carbon-coated Ag dispersion B-3)
[0117] 80 g of carbon-coated Ag particles, 4 g of dispersant "DISPERBYK (registered trademark)"-21116 (manufactured by BYK-Chemie) and 200 g of PGMEA were mixed and mixed using a homogenizer at 1,200 rpm for 30 minutes. Then, a high-pressure wet medium-free micronizer "Nanomizer" (Nanomizer Co., Ltd.) was used for dispersion treatment to obtain a carbon-coated Ag dispersion B-3 having an average particle size of 0.2 μm and a conductive particle content of 28.2 wt%.
[0118] (Synthesis Example 6: Tin Oxide Dispersion Liquid B-4)
[0119] 40 g of tin oxide particles, 4 g of a dispersant "DISPERBYK (registered trademark)" - 21116 (manufactured by BYK-Chemie), and 200 g of PGMEA were mixed, and a mixing treatment at 1,200 rpm for 30 minutes was performed using a homogenizer. Then, a dispersion treatment was further performed using a high-pressure wet medium-free atomizer "Nanomizer" (Nanomizer Co., Ltd.) to obtain a tin oxide dispersion liquid B-4 having an average particle diameter of 0.2 μm and a conductive particle content of 16.4% by weight.
[0120] (Example 1)
[0121] A 5 wt% toluene solution of a silicone-based mold release agent "Tesfine (registered trademark)" 303 was spin-coated on a glass substrate at a rotational speed of 2,000 rpm, and then heated at 140 °C for 30 minutes using a drying oven to fabricate a transfer substrate 1 having a mold release layer.
[0122] 10 g of the organic component solution A-1 obtained in Synthesis Example 1, 1.07 g of a thermosetting resin N-770, and 36.8 g of the carbon black dispersion liquid B-1 obtained in Synthesis Example 3 were mixed using a spin-revolution vacuum mixer "Awatori Rentaro (registered trademark)" ARE-310 (manufactured by THINKY Corporation) to obtain a photosensitive composition 1 having a conductive particle content of 30.2% by weight (20.0% by volume) in the solid component. Here, the solid component means the components other than the solvent in the photosensitive composition.
[0123] Next, the photosensitive composition 1 was pattern-coated on the transfer substrate 1 obtained by the above method using an inkjet coating device so that the diameter was 100 μm and the thickness after drying was 2 μm to form bump patterns. A total of 100 bump patterns, 10 in each of the horizontal and vertical directions, were fabricated in a 3 mm square area on the transfer substrate 1. Then, it was dried at 100 °C for 10 minutes using a drying oven. The contact area of each bump pattern with the transfer substrate 1 was 7,850 μm 2 。
[0124] Next, the transfer substrate 1 formed with the bump pattern is placed opposite to the transferred glass substrate marked with a cross mark at the desired position in advance, so that the distance between the substrates becomes 50 μm, and the intersection of the cross mark on the transferred glass substrate coincides with the center of the bump, and laser irradiation is performed from the back side of the transfer substrate 1. Regarding the laser, the wavelength is 532 nm, the beam size is set to 1.5 times that of the bump, and the irradiation is performed at two levels of energy, 300 mJ and 600 mJ. Thus, the bump of the transfer substrate 1 is transferred to the transferred glass substrate, thereby obtaining a glass substrate with bumps. Using the obtained glass substrate with bumps, the position accuracy is evaluated by the above method.
[0125] Similarly, after 10 bumps with a diameter of 100 μm were formed into a row at intervals of 100 μm in a 3 mm square area on the transfer substrate 1, the bumps were transferred to the Au electrodes of the printed wiring board, which was another substrate to be transferred, by laser irradiation. The laser was irradiated with a wavelength of 532 nm, a beam size of 1.2 times that of the bump, and an energy of 300 mJ. Thus, a Figure 3 The printed wiring board with bumps shown has bumps 1 on electrodes 7 of printed wiring board 6. The obtained printed wiring board with bumps was used to evaluate the conductivity and connection reliability by the above-mentioned method.
[0126] (Example 2)
[0127] The photosensitive composition 1 prepared in Example 1 was applied to the transfer substrate 1 prepared in Example 1 so that the film thickness after drying was 2 μm, and dried in a drying oven at 100° C. for 10 minutes. Then, the photosensitive composition 1 prepared in Example 1 was applied to the transfer substrate 1 prepared in Example 1 at an exposure dose of 1,000 mJ / cm 2 through a mask corresponding to a pattern described later. 2 Exposure was performed and alkali development was performed to form a bump pattern. Each bump pattern was set to have a diameter of 100 μm, and 10 bump patterns were made in a 3 mm square area on the transfer substrate 1, with a total of 100 bump patterns. The contact area of each bump pattern with the transfer substrate 1 was 7,850 μm 2 .
[0128] Using the transfer substrate 1 on which the bump pattern was formed obtained by the above method, a glass substrate with bumps and a printed wiring board with bumps were produced and evaluated in the same manner as in Example 1.
[0129] (Examples 3 to 6)
[0130] A glass substrate with bumps and a printed wiring board with bumps were prepared and evaluated in the same manner as in Example 2 except that the diameter of the bump was changed and the contact area per bump with the release layer was changed as shown in Table 1.
[0131] (Example 7)
[0132] Except having changed the thickness of the bump as shown in Table 1, a glass substrate with bumps and a printed wiring board with bumps were produced and evaluated in the same manner as in Example 4.
[0133] (Examples 8 to 14)
[0134] A glass substrate with bumps and a printed wiring board with bumps were prepared and evaluated in the same manner as in Example 4 except that a release layer was formed on the glass substrate using the material shown in Table 1 instead of the silicone release agent "Tesfine (registered trademark)" 303.
[0135] (Examples 15 to 17)
[0136] A glass substrate with bumps and a printed wiring board with bumps were prepared and evaluated in the same manner as in Example 4, except that the Ag particle dispersion B-2, carbon-coated Ag dispersion B-3 and tin oxide dispersion B-4 obtained in Synthesis Examples 4 to 6 were used instead of the carbon black dispersion B-1 obtained in Synthesis Example 3.
[0137] (Example 18)
[0138] A glass substrate with bumps and a printed wiring board with bumps were prepared and evaluated in the same manner as in Example 4 except that the organic component solution A-2 obtained in Synthesis Example 2 was used instead of the organic component solution A-1 obtained in Synthesis Example 1.
[0139] (Examples 19 to 24)
[0140] A glass substrate with bumps and a printed wiring board with bumps were prepared and evaluated in the same manner as in Example 4 except that the conductive particle content in the carbon black dispersion B-1 and the thermosetting resin content in the organic component solution A-1 were changed as shown in Table 2.
[0141] (Examples 25-26)
[0142] Except having changed the electrode of a printed wiring board as described in Table 2, the glass substrate with bumps and the printed wiring board with bumps were produced and evaluated in the same manner as in Example 15.
[0143] (Examples 27-28)
[0144] Except having changed the electrode of a printed wiring board as described in Table 2, the glass substrate with bumps and the printed wiring board with bumps were produced and evaluated in the same manner as in Example 4.
[0145] (Example 29)
[0146] After mounting a silicon chip with electrodes for evaluating conductivity on a printed wiring board produced in the same manner as in Example 4, a printed wiring board with bumps was newly produced next to the mounted silicon chip in the same manner as in Example 4 and evaluated.
[0147] (Comparative Example 1)
[0148] A glass substrate with bumps and a printed wiring board with bumps were produced and evaluated in the same manner as in Example 23 except that the release layer was not provided.
[0149] (Comparative Examples 2 to 3)
[0150] A glass substrate with bumps and a printed wiring board with bumps were produced and evaluated in the same manner as in Example 28 and Example 26, respectively, except that the release layer was not provided.
[0151] Tables 1 to 3 show the main configurations and evaluation results of each example and comparative example.
[0152] [Table 1]
[0153]
[0154] [Table 2]
[0155]
[0156] [Table 3]
[0157] [Table 3]
[0158]
[0159] Description of Reference Numerals
[0160] 1: Bump
[0161] 2: Glass substrate
[0162] 3: Laser
[0163] 4: Transfer substrate
[0164] 5: Release layer
[0165] 6: Printed wiring board
[0166] 7: Electrodes of printed wiring boards
[0167] 8: Silicon Chip
[0168] 9: Electrodes of silicon chips
[0169] 10: Bump
[0170] 11: Transfer substrate
[0171] 12: Laser
[0172] 13: Transfer substrate
[0173] 14, 14': Electronic components
[0174] 15: Electrodes of electronic components
Claims
1. A substrate having a bump pattern containing an organic component and conductive particles on a release layer of a transfer substrate having a release layer.
2. The substrate according to claim 1, wherein The transfer substrate having a release layer has a peeling force of 100 to 5,000 mN / 50 mm at 25°C.
3. The substrate according to claim 1 or 2, wherein The content of the conductive particles in the bump pattern is 10 to 40 volume %.
4. The substrate according to claim 1 or 2, wherein The OD value of the bump pattern is 0.5-3.
5. The substrate according to claim 1 or 2, wherein The aspect ratio of the bump pattern is 0.1 to 0.4, and the contact area between each bump pattern and the release layer is 25 to 500 μm 2 .
6. The substrate according to claim 1 or 2, wherein: The conductive particles include carbon black and / or metal particles having a carbon coating layer.
7. The substrate according to claim 1 or 2, which is used for repair.
8. The method for producing a substrate according to claim 1 or 2, comprising a step of exposing a photosensitive composition containing an organic component and conductive particles (exposure step) and a step of developing the composition (development step).
9. A method for producing a structure with bumps, comprising the step of transferring bumps to an electrode portion of a substrate with electrodes or an electronic component by irradiating the substrate according to claim 1 or 2 with laser light from the side opposite to the release layer (bump transfer step).
10. The method for manufacturing a structure with bumps according to claim 9, wherein: The substrate with electrodes is a substrate with electrodes on which electronic components are mounted.
11. A method for manufacturing a structure with bumps, comprising: a process of forming bumps containing organic components and conductive particles on a release layer of a transfer substrate having a release layer (bump forming process); and a process of irradiating a laser from the opposite side of the release layer of the transfer substrate to transfer the bumps to an electrode portion of a substrate with electrodes or an electronic component (bump transferring process).
